An Empirical Study of Students’ Learning Interest in the Smart Library School Program in Thailand - Natcha Beam; Pimchanok; Boon-Nam (Madako Elementary School, 2025)
This study examines the increase in primary school students’ library visitation interest through the implementation of a smart library at Bangkok Patana School in Songkha, Thailand. The study aims to identify the effectiveness of the smart library in fostering visitation interest and to understand the factors influencing it. A qualitative approach was employed using a case study design, involving 15 students, 3 teachers, and the head librarian, all selected purposively. Data were collected through in-depth interviews and participatory observation. The findings indicate that the implementation of the smart library significantly increased students’ visitation frequency, from an average of twice per week to 5.4 times per week. Furthermore, 87% of students identified the key factors driving their visits, including user-friendliness (85%), content relevance and quality (80%), accessibility and compatibility (82%), engagement and interactivity (85%), and system reliability and performance (86%). These results suggest that the smart library plays a significant role in enhancing digital literacy and self-regulated learning. The study’s contribution lies in providing an empirical mapping of the effectiveness of digital libraries in primary schools and identifying the key elements that influence students’ visitation interest within the context of digital elementary education.